Effectiveness of Finger Hold Relaxation Technique on Pain in Mothers Who Have Sex 640-645 - Etni Yeyem Sumaila; Rifzul Maulina; Anik Sri Purwanti (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2025)
Post-cesarean section (CS) pain is a common issue faced by postpartum mothers, significantly affecting their recovery process and overall well-being. Effective pain management is crucial to enhance recovery and improve quality of life. One promising non-pharmacological approach gaining attention is the finger hold relaxation technique, which has been shown to alleviate various forms of pain. This study aimed to assess the effectiveness of the finger hold relaxation technique in reducing post-CS pain. A quasi-experimental design was used with two groups: an intervention group that received the finger hold relaxation technique and a control group that did not receive the intervention. The study involved 60 post-CS mothers, randomly divided into the two groups. Pain levels were measured before and after the intervention using the Numeric Rating Scale (NRS). Data analysis was performed using the Mann-Whitney U test. Results indicated a significant decrease in pain levels in the intervention group compared to the control group (p < 0.05). The average pain score in the intervention group before the intervention was 7.5, which decreased to 4.2 after the intervention. In contrast, the control group exhibited relatively stable pain scores, with an average of 7.3 before the intervention and 6.9 after. The Mann-Whitney U test confirmed a significant difference, with a p-value of 0.01, indicating that the finger hold relaxation technique had a significant effect on reducing post-CS pain. In conclusion, the finger hold relaxation technique is effective in reducing pain in post-CS mothers. It is recommended that this technique be incorporated into post-operative care programs to enhance maternal comfort and facilitate faster recovery.